A pathologic role for angiotensin II and endothelin-1 in cardiac remodelling and ischaemia and reperfusion injury in a rat model of the metabolic syndrome - Smith, Wayne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2006.